Bioburden in sleeping environments from Portuguese dwellings. (15th March 2021) - Viegas, Carla; Dias, Marta; Monteiro, Ana; Faria, Tiago; Lage, Joana; Carolino, Elisabete; Caetano, Liliana Aranha; Gomes, Anita Quintal; Almeida, Susana Marta; Verde, Sandra Cabo; Belo, Joana; Canha, Nuno
Abstract: A wider characterization of indoor air quality during sleep is still lacking in the literature. This study intends to assess bioburden before and after sleeping periods in Portuguese dwellings through active methods (air sampling) coupled with passive methods, such as electrostatic dust cloths (EDC); and investigate associations between before and after sleeping and bioburden. In addition, and driven by the lack of information regarding fungi azole-resistance in Portuguese dwellings, a screening with supplemented media was also performed. The most prevalent genera of airborne bacteria identified in the indoor air of the bedrooms were Micrococcus (41%), Staphylococcus (15%) and Neisseria (9%). The major indoor bacterial species isolated in all ten studied bedrooms were Micrococcus luteus (30%), Staphylococcus aureus (13%) and Micrococcus varians (11%). Our results highlight that our bodies are the source of the majority of the bacteria found in the indoor air of our homes. Regarding air fungal contamination, Chrysosporium spp. presented the highest prevalence both in after the sleeping period (40.8%) and before the sleeping period (28.8%) followed by Penicillium spp. (23.47% morning; 23.6% night) and Chrysonilia spp. (12.4% morning; 20.3% night). Several Aspergillus sections were identified in air and EDC samples. However, none of the fungal species/strains ( Aspergillu s sections Fumigati, Flavi, Nidulantes and Circumdati ) were amplified by qPCR in the analyzed EDC. The correlations observed suggest reduced susceptibility to antifungal drugs of some fungal species found in sleeping environments. Toxigenic fungal species and indicators of harmful fungal contamination were observed in sleeping environments. Graphical abstract: Image 1 Highlights: The most prevalent bacteria found in bedrooms indoor air was Micrococcus luteus. Human microbiota is the source of the majority of the bacteria found indoors. Several Aspergillus sections were identified indoors and indicators of harmful contamination were observed. Reduced susceptibility to antifungal drugs of some fungal species was found. Sleeping environments should be assessed not only for research but also for clinical purposes. Abstract : Capsule: Our bodies are the source of the majority of the bacteria found in the sleeping environments and toxigenic fungal species and indicators of harmful contamination were observed.